Pharmacokinetics of difloxacin after single intravenous, oral and intramuscular administration in pigeons - Yang-Guang Jin; Yue Liu; Yan-Ni Zhang; Yu-Xin Chen; Long-Ji Sun; Shi-Hao Li; Wen-Rui Wang; Fan Yang (Poultry Science)
This study aimed to investigate the pharmacokinetics of difloxacin in pigeons following oral (PO), intramuscular (IM), and intravenous (IV) administration. Thirty pigeons were randomly divided into three groups (IM, IV, and PO; n = 10 per group). Difloxacin was administered at 10 mg/kg body weight (BW) via each route. Blood samples were collected at various intervals from 0 to 48 h, and plasma was analyzed for difloxacin concentrations using a validated high-performance liquid chromatography (HPLC) method. Pharmacokinetic parameters were determined using Phoenix software and a non-compartmental analysis (NCA) approach. After PO and IM administration, peak plasma concentrations (Cmax) were observed as 1.81 ± 0.47 and 6.52 ± 1.62 μg/mL, occurring at 2.60 ± 0.97 and 0.63 ± 0.24 h, respectively. Bioavailability (F) was 38.35 % ± 10.45 % for PO and 90.25 % ± 26.14 % for IM administration. Following IV administration, difloxacin was widely distributed, with a volume of distribution (VZ) of 2.52 ± 0.65 L/kg and a steady-state volume of distribution (VSS) of 1.87 ± 0.27 L/kg. Difloxacin exhibited slow elimination, with elimination half-lives (t1/2λzs) of 1.61 ± 0.3, 2.64 ± 0.64, and 4.27 ± 1.14 h after IM, PO, and IV administration, respectively. Based on the AUC/MIC ratios calculated here, the current IM or IV administration at 10 mg/kg BW is effective against bacterial infections with MIC values ≤ 0.1 μg/mL, while the current oral dose (10 mg/kg BW) may be insufficient, particularly for infections caused by pathogens with MIC values exceeding 0.1 μg/mL.